Proposal to improve the current business model of the recycling centers in Guayaquil (LACCEI, 2024)
In the last 30 years the increase in waste has been evident. In this sense, recycling not only makes sense from an environmental point of view, but also from an economic point of view, this type of activity reaches entrepreneurs, collectors and companies that seek to develop the circular economy. For this reason, this study seeks to identify the business model currently used by recycling collection centers in Guayaquil and, based on this, propose the most appropriate model for its growth and sustainable development. For this reason, the design of the study was based on a qualitative approach of an exploratory nature in the city of Guayaquil in order to outline the business model of the recyclers, through the Business Model Canvas (BMC) of Osterwalder Pigneur. The model was obtained through interviews with questions focused on the nine components of the BMC, which made it possible to investigate information clearly not specified in other sources. Based on the results, it was found that several collection centers have reduced physical spaces for material storage and their most important means of communication is the mobile phone with very little use of social networks. Based on this, it is proposed that the recyclers group people by needs or behaviors in such a way that they include companies, shopping centers, schools, universities, the public sector and the private sector.